Industrialization of crustaceans for obtaining chitosan in effect ointment wound healing - García Zapata, Teonila (2008)
Between 20 to 30, the weight of the kind of crust,Crustaceans is used human food, no human is the rest consisting of viceras and exoskeleton, especially the carapaces of hairy crab, crab raped her ceo, jaivas, lobster, shrimp that are found in greater numbers along the coasts of thePeruvian coast,which are regarded as environmental pollutants (waste ) These compounds are commercially valuable untapped, which can be used to obtain two biopolymers specialized high valueadded established worldwide: chitin and its derivative functional, the chitosan, giving a natural product with therapeutic properties that help in the treatment of burns. The objective of this research is to develop and introduce the product in ointment or cream to go into competitionwith chemicals to higher costs,whilemaintaining the same properties, such as the stimulation of growth of new tissue and help heal the wounds.